2017
DOI: 10.1007/s00335-017-9728-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences in the aryl hydrocarbon receptor and CYP1A2 affect sensitivity to developmental polychlorinated biphenyl exposure in mice: relevance to studies of human neurological disorders

Abstract: Polychlorinated biphenyls (PCBs) are persistent organic pollutants that remain a human health concern with newly discovered sources of contamination and ongoing bioaccumulation and biomagnification. Children exposed during early brain development are at highest risk of neurological deficits, but highly exposed adults reportedly have an increased risk of Parkinson's disease. Our previous studies found allelic differences in the aryl hydrocarbon receptor and cytochrome P450 1A2 (CYP1A2) affect sensitivity to dev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…Gestational and lactational exposure to a mixture of DL (PCBs 77, 105, 118, 126, and 169) and NDL (PCBs 138, 153, and 180) congeners at 5.6 mg/kg/d in the maternal diet reduced serum thyroxine (T4) at PND 14 in offspring of all three genotypes. However, Ahr b /Cyp1a2 -/mice exhibited a greater T4 reduction than the other two genotypes [177]. Postnatal development of the cerebellum is particularly sensitive to TH insufficiency [175][176][177][178], and consistent with this, PCB-exposed Ahr b /Cyp1a2 -/mice exhibited defects in cerebellar structure at PND 25 [177].…”
Section: Arylhydrocarbon Receptor (Ahr) As a Molecular Target In Pcb mentioning
confidence: 73%
See 3 more Smart Citations
“…Gestational and lactational exposure to a mixture of DL (PCBs 77, 105, 118, 126, and 169) and NDL (PCBs 138, 153, and 180) congeners at 5.6 mg/kg/d in the maternal diet reduced serum thyroxine (T4) at PND 14 in offspring of all three genotypes. However, Ahr b /Cyp1a2 -/mice exhibited a greater T4 reduction than the other two genotypes [177]. Postnatal development of the cerebellum is particularly sensitive to TH insufficiency [175][176][177][178], and consistent with this, PCB-exposed Ahr b /Cyp1a2 -/mice exhibited defects in cerebellar structure at PND 25 [177].…”
Section: Arylhydrocarbon Receptor (Ahr) As a Molecular Target In Pcb mentioning
confidence: 73%
“…However, Ahr b /Cyp1a2 -/mice exhibited a greater T4 reduction than the other two genotypes [177]. Postnatal development of the cerebellum is particularly sensitive to TH insufficiency [175][176][177][178], and consistent with this, PCB-exposed Ahr b /Cyp1a2 -/mice exhibited defects in cerebellar structure at PND 25 [177]. In other studies by this group, exposure to this same PCB mixture on GD 10 and PND 5 resulted in learning and memory deficits in NOR and MWM tasks in both Ahr b /Cyp1a2 -/- [178] and Ahr d /Cyp1a2 -/-mice [179], enhanced startle response in Ahr d /Cyp1a2 -/mice [179], and increased locomotor activity in Ahr b /Cyp1a2 -/mice [178].…”
Section: Arylhydrocarbon Receptor (Ahr) As a Molecular Target In Pcb mentioning
confidence: 84%
See 2 more Smart Citations
“…This study not only increased the power of GWAS, but also provided critical mechanistic underpinning to the identified susceptibility loci. The interplay between the status of aryl hydrocarbon receptor (AHR), cytochrome P450 1a2, exposure to polychlorinated biphenyls (PCB), and neurotoxicity was explored using genetically-modified mouse models by Klinefelter et al (Klinefelter et al 2018). The authors were especially interested in the effects of in utero exposures and showed that AHR is a modifier of developmental neurotoxicity of PCB, but not for Parkinson’s disease.…”
mentioning
confidence: 99%